Formulações nanoestruturadas contendo rutina: desenvolvimento, atividade antioxidante in vitro e efeito sobre a cicatrização cutânea - Almeida, Juliana Severo de (2010)
This work had as main objective the development of nanostructured formulations containing rutin, using nanoparticles prepared with alternative vegetables oils. In the first chapter it was demonstrated the feasibility of preparing nanocapsules and nanoemulsions using grape seed or almond kernel oil. Nanocapsule suspensions and nanoemulsions were prepared by the interfacial deposition of preformed polymer and spontaneous emulsification, respectively. All formulations presented nanometric mean size, polydispersity index below 0.30, negative zeta potential, pH values between 6.5 and 7.5 remaining stable after 6 storage months. These formulations promoted the protection of the active against UV degradation, regardless of the type of the oily phase or vesicle. In the second chapter, formulations prepared with grape seed oil were selected for the development of rutin-loaded nanoparticles, as well as to evaluate its in vitro antioxidant activity and photostability. All formulations presented nanometric size, low polydispersity index, acid pH values, negative zeta potential and encapsulation efficiency close to 100 %. Nanoparticles were able to protect rutin against UV photodegradation, if compared to rutin ethanolic solution. In the study of the in vitro antioxidant activity, rutin-loaded nanocapsules and nanoemulsions showed a lower rutin decay rate compared to the rutin ethanolic solution when exposed to UV radiation in the presence of OH radical. However, its presence in nanocapsules led to a prolonged in vitro antioxidant activity compared to the rutin-loaded nanoemulsions. Finally, in the third chapter we studied the development of hydrogels containing rutin (free or associated to polymeric nanocapsules). Their activity on the cutaneous wound healing in rats was evaluated. The developed formulations showed adequate properties regarding their cutaneous administration. In vivo response concerning the healing effect of hydrogels was evaluated by the regression of skin lesions after six days of treatment. Markers of oxidative stress in the lesions of rats were also evaluated, as levels of lipid peroxidation analyzed by the method of thiobarbituric acid reactive substances (TBARS), determination of protein carbonyls levels, total proteins levels, glutathione (GSH) levels, vitamin C and evaluation of the antioxidant enzyme catalase (CAT). This last chapter showed for the first time the feasibility of the dermatological use of such formulations containing rutin to promote the in vivo wound healing.